Nitrogen Fertilization and CaC03 Interaction on Corn (Zea .mays L.) Grain and Dry Matter Yields and their Residual Effects on Al-Marj Soil, Libya - Elamin, E A; Tiblib, M.A El; Gaziri, M M EL (Annals of Arid Zone, 2016)
Two field trials were conducted at Al-Marj Research Center, north-east / Libya, during the .summers of .1996 and 1997 to examine the effects of nitrogen fertilizers on com grain and dry matter yields grown in Al-Marj soil in Libya (fine mixed thermic, typic Xeroll) amended with different CaC03 levels. Two nitrogen fertilizer sources (urea and diammonium phosphate) wer6 used at different rates (0, 80, 160 kg N ha-’). The CaC03 treatments were 1, 6 and 12% based on the 15 cm furrow slice. A basal phosphorus dose of 46 kg P205 h? I was applied to all experimental plots before planting. The experimental plots were arranged in a’ split-split plot design with three replications. The parameters measured included com grain weight, shoot dry matter yield, soil contents of N, P, K, Ca andÂ· Mg. Urea was significantly superior over diammonium phosphate and increasing nitrogen levels significantly increased. com grain and dry matter yields. CaC03 significantly decreased the shoot dry matter and com grain yields. Nitrogen. fertilizer rates and their interactions with CaC03 significantly reduced shoot dry matter and com grain yields. The CaC03, nitrogen source and nitrogen level interaction was significant on the grain and dry matter yield. The negative effect of CaC03 on yield was associated with concomitant significant reduction in soil N, P, and Mg contents, but a significant increase in the soil-Ca content was observed. The main nitrogen effect was significant on soil nitrogen and phosphorus, while it induced no significant effectÂ· on soil potassium. The interactions between CaC03, nitrogen source and levels were significant on the soil nitrogen, phosphorus, calcium and magnesium. However, the soil levels of these nutrients were considered’ insufficient for optimum com growth. It is thus, concluded that the reduction of soil N by CaC03 in ,fertilized soils might have been the major cause of com dry matter and grain yield reductions.